2018
DOI: 10.1038/s41388-018-0492-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of solute carrier family 7 member 2 exacerbates inflammation-associated colon tumorigenesis

Abstract: Solute carrier family 7 member 2 (SLC7A2, also known as CAT2) is an inducible transporter of the semi-essential amino acid L-arginine (L-Arg), which has been implicated in wound repair. We have reported that both SLC7A2 expression and L-Arg availability are decreased in colonic tissues from inflammatory bowel disease patients and that mice lacking Slc7a2 exhibit a more severe disease course when exposed to dextran sulfate sodium (DSS) compared to wild-type (WT) mice. Here, we present evidence that SLC7A2 plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 51 publications
3
45
0
Order By: Relevance
“…Unlike in other studies [21], active CD here was associated with diminished systemic arginine concentrations and, like in other studies [24], no difference in the case of UC was observed. Knockout studies have shown that arginine transporters, and thus arginine, are necessary to reduce mucosal inflammation and the incidence of colitis-associated tumorigenesis [20]. Accordingly, dietary arginine is claimed to be beneficial in animal models of colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in other studies [21], active CD here was associated with diminished systemic arginine concentrations and, like in other studies [24], no difference in the case of UC was observed. Knockout studies have shown that arginine transporters, and thus arginine, are necessary to reduce mucosal inflammation and the incidence of colitis-associated tumorigenesis [20]. Accordingly, dietary arginine is claimed to be beneficial in animal models of colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Its deprivation is viewed as a way to starve the arginine auxotrophic tumors [11,18]. In IBD, on the contrary, arginine supplementation is advocated both for chemoprevention of colitis-associated carcinogenesis and for reduction of colonic inflammation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms whereby CLIC6 expression may positively impact on survival remain obscure. Conversely, SLC7A2 (which was enriched in patients with good prognosis) is known for its anti-inflammatory effects, 50 at least in part linked to its key role in the immunosuppressive activity of myeloid-derived suppressor cells. 51 These observations lend further support to the notion that chronic, indolent Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Blautia has also been associated with an inflamed gut in Crohn's disease and other clinical conditions 36,37 . Additionally, alterations in solute carrier expression as present in the Mexican population 12 have been observed in the development of irritable bowel disease and have been linked to inflammation 38,39 .…”
Section: Discussionmentioning
confidence: 99%